Análise econômica da aplicação de nitrogênio e fósforo na cultura do milho no município de Barra Mansa, estado do Rio de Janeiro - Gomes, Guarany Carlos; Basílio Costalonga Seraphim, João; Coelho de Alvarenga, Sônia (Revista Ceres, 2025)
Underdeloped countries are faced with the widespread problem of rapid population growth. Brazil,whose population is increasing at the rate of 3 percent per year, is no exception. New methods of increasing food supplier must therefore be givem the highest priorities.